2017
DOI: 10.1590/0001-3765201720150702
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity and bacterial membrane destabilization induced by Annona squamosa L. extracts

Abstract: This study aimed to further investigate the cytotoxicity against tumor cell lines and several bacterial strains of Annona squamosa and its mode of action. Methanol extracts of A. squamosa leaves (ASL) and seeds (ASS) were used. ASL showed significant antibacterial activity against S. aureus, K. pneumoniae and E. faecalis with MIC values of 78, 78 and 39 µg/mL respectively. Moreover, ASL exhibited significant biofilm disruption, rapid time dependent kinetics of bacterial killing, increased membrane permeability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 53 publications
2
15
0
4
Order By: Relevance
“…Indeed, infections caused by S. aureus have reached epidemic proportions globally owing to its strong multi-resistance [ 62 ]. These results were consistent with those of Pinto et al [ 58 ] who found the significant antibacterial activity of the methanolic extract of A. squamosa leaves and seeds against S. aureus , K. pneumoniae , and E. faecalis strains. Vijayalakshmi and Nithiya evaluated the antibacterial activity of A. squamosa fruit extracts, which exhibited more potent activity against gram-negative bacteria than gram-positive bacteria.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Indeed, infections caused by S. aureus have reached epidemic proportions globally owing to its strong multi-resistance [ 62 ]. These results were consistent with those of Pinto et al [ 58 ] who found the significant antibacterial activity of the methanolic extract of A. squamosa leaves and seeds against S. aureus , K. pneumoniae , and E. faecalis strains. Vijayalakshmi and Nithiya evaluated the antibacterial activity of A. squamosa fruit extracts, which exhibited more potent activity against gram-negative bacteria than gram-positive bacteria.…”
Section: Discussionsupporting
confidence: 93%
“…However, Zorofchian Moghadamtousi et al [57] demonstrated that the ethyl acetate extract of A. muricata leaves conspicuously blocked the migration of HCT-116 cells, suggesting the similar chemical composition of the leaves of both species (A. muricata and A. squamosa). A more recent study by Pinto [58] investigated the effects of A. squamosa seeds and leaves extracts on different tumor and non-tumor cells' ability to form colonies. The authors reported that both extracts ultimately reduced the colonogenic survival of MCF-7 and HCT-116 cells, while both extracts showed lower activity against non-tumor cells (VERO).…”
Section: Discussionmentioning
confidence: 99%
“…For this study, 10 10 CFU per ml of exponentially growing bacterial cultures were incubated with different concentrations of Cr‐SPs (0·5–8 mg ml −1 ) along with a control sample at 37°C in GM3 media. The growth was measured from 0 h till 48 h by recording the optical density at 595 nm at different time points and the growth curve is obtained by plotting absorbance against time (Pinto et al ). CFU assay was performed as mentioned in Zhou et al .…”
Section: Methodsmentioning
confidence: 99%
“…Saline suspensions of freshly grown bacterial strains (10 8 CFU mL -1 ) were inoculated with different concentrations of psychorubrin (MIC, 0.5MIC, and 0.25MIC values) supplemented with MHB. Optical density (OD) at 600 nm was recorded in a spectrophotometer (Multiskan Go, Thermo Scientific, Waltham, MA, United States) at 2, 4, 6, 8, and 24 h of bacterial growth at 37°C as before ( Pinto et al, 2017a , b ). Graphs of turbidity versus incubation time were plotted.…”
Section: Methodsmentioning
confidence: 99%
“…Because antimicrobial resistance and biofilm formation are a global public health challenge, there is a striking need of development of new biologically active molecules against multidrug-resistant bacteria and the adoption of medicinal crude extracts of plants to treat infectious diseases ( Subramani et al, 2017 ). In this context, our group has been studying different potential bioactive antibacterial compounds ( Pinto et al, 2017a , b ), including a natural product termed psychorubrin, a napthoquinone commonly found in a variety of plants ( Fabri et al, 2009 , 2012 ).…”
Section: Introductionmentioning
confidence: 99%